Implementation of Technology-Based Quantum Learning Method In Learning Arabic Reading Skills / Penerapan Metode Quantum Learning Berbasis Teknologi Dalam Pembelajaran Maharah Qiraah - Nuril Mufidah; Farida Nur Fatih (Bumi Lingua Edu Center, 2025)
The technology-based quantum learning method in education is an approach that combines the principles of quantum learning with the use of technology. Quantum learning is a teaching methodology that emphasizes active learning, experiential learning, and independent learning. This study aims to describe the implementation of the quantum learning method in Maharah Qiraah learning, the use of the Aljazeera website in Maharah Qiraah learning, and students' perceptions of the quantum learning method in technology-based Maharah Qiraah learning. This research uses a qualitative descriptive method. The research subjects are 34 third-semester students from the Arabic Language Education program of 2023, enrolled in the Maharah Qiraah course. Data collection techniques include direct observation of learning activities and interviews with students. Data analysis adopts Grounded Theory. The results of the study show that the quantum learning method is an appropriate choice in Maharah Qiraah learning. Supported by the Al Jazeera website, technology helps students improve their Qiraah skills. Students also believe that the quantum learning method can enhance their creativity and reading skills, further aided by the ease of learning provided by technology.